Microvesicles derived from leukocytes in the peripheral blood of patients with external genital endometriosis - M. I. Yarmolinskaya; E. I. Durneva; K. L. Markova; V. A. Mikhailova; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2022)
Endometriosis is a chronic gynecological disease, which poses a serious problem in terms of diagnosis and treatment. Despite decades of research, there are no specific signs and symptoms and no blood tests to clinically confirm the diagnosis, which makes timely diagnosis and treatment difficult. Therefore, the search for new markers for early non-invasive diagnosis of the disease remains relevant. Various subcellular structures involved in intercellular communication, in particular, microvesicles, can be considered promising biological markers for external genital endometriosis. The aim of this work was to assess the composition of microvesicles derived from leukocytes in the peripheral blood of patients with stage I-II of external genital endometriosis and the possibility of their use as markers of non-invasive diagnosis of peritoneal forms of endometriosis. The study involved 97 women aged 26-40 with stage I-II of external genital endometriosis, whose diagnosis was established intraoperatively and confirmed histologically. Pain syndrome was noted in all patients of the main group, with infertility also detected in 73.2% of the patients. The control group consisted of 20 patients, whose average age was 25.5±1.1 years, who were examined in connection with male infertility factor before the in vitro fertilization, and in whom, on the basis of intraoperative examination, presented no gynecological diseases, and no pain syndrome. Before the surgical intervention, peripheral blood was taken from all patients to determine the content of microvesicles derived from leukocytes. To isolate microvesicles, we used the previously described by M.P. Gelderman and J. Simak method. It was found that patients with stage I-II of external genital endometriosis experience an increase in the number of CD14+, CD16+ and CD54+CD14+ microvesicles in the peripheral blood by 1.1, 1.38 and 1.55 times, respectively, as well as a decrease in the number of CD45+CD4+, CD3+CD4+, CD3+CD8+ microvesicles by 1.2, 4 and 1.5 times, respectively, compared with patients from the control group. Therefore, in patients with stage I-II of external genital endometriosis, an increase in the relative number of CD54+CD14+ microvesicles in the peripheral blood above 5.22% can serve as a marker for early non-invasive diagnosis of the disease with sensitivity of 80.5% and specificity of 71%.